2021
DOI: 10.1111/cpr.13072
|View full text |Cite
|
Sign up to set email alerts
|

EZH2‐mediated inhibition of KLF14 expression promotes HSCs activation and liver fibrosis by downregulating PPARγ

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…We provided strong evidence of fibrotic lesions, inflammatory infiltration, and cell degeneration in the heart, liver, and kidney of KLF14 −/− mice, which is likely due to the low KLF14 and POLD1 levels in the tissues. Moreover, recently reported findings revealed that KLF14 exerted a protective role in cardiovascular disease and multiple chronic liver diseases by inhibiting inflammation and fibrosis, which is consistent with our results 63 . Furthermore, we found atrophy in the spleen of KLF14 −/− mice with low KLF14 and POLD1 expression compared with WT mice.…”
Section: Discussionsupporting
confidence: 93%
“…We provided strong evidence of fibrotic lesions, inflammatory infiltration, and cell degeneration in the heart, liver, and kidney of KLF14 −/− mice, which is likely due to the low KLF14 and POLD1 levels in the tissues. Moreover, recently reported findings revealed that KLF14 exerted a protective role in cardiovascular disease and multiple chronic liver diseases by inhibiting inflammation and fibrosis, which is consistent with our results 63 . Furthermore, we found atrophy in the spleen of KLF14 −/− mice with low KLF14 and POLD1 expression compared with WT mice.…”
Section: Discussionsupporting
confidence: 93%
“…This process was accompanied by the downregulation of H3K9me3 and upregulation of H3K4me3 in the promoter region of PPARγ2 ( Erener et al, 2012 ), suggesting that PARP may be involved in regulating adipocyte differentiation by affecting epigenetic modifications. In line with this phenomenon, EZH2 coincides with the ability to catalyze histone methylation in the promoter region of PPARγ2, the result of which promotes processes such as liver fibrosis ( Du et al, 2021 ) and pancreatic cancer cell proliferation ( Hu et al, 2021 ). Interestingly, our previous research has also found EZH2 inhibitor GSK126 upregulates the expression level of fatty acid synthesis related genes and results in lipid droplet accumulation in liver ( Zhang et al, 2022 ).…”
Section: Association Between Ezh2 and Poly Adp-ribose Polymerase In T...mentioning
confidence: 76%
“…Perugorria et al demonstrated that histone methyltransferase ASH1, as a key transcriptional active component in the MeCP2 regulatory pathway, jointly regulates the expression of multiple fibrosis-related genes (CFTR and PPARs) and ultimately stimulates liver fibrosis. 25,26 Except that histone methylation may be the "cause" of the progress of liver fibrosis, the changes in the microenvironment during the progress of liver fibrosis can also result in abnormal regulation of histone methylation. For example, alcohol intake in alcoholic liver disease causes the trimethylation of the histone H3K4 (H3K4me3) of HSC.…”
Section: Antagonizing Ezh2 Can Synergistically Inhibit Hepatic Stella...mentioning
confidence: 99%